2018
DOI: 10.1142/s0219455418500736
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Point Response for Modal Identification of Bridges by a Moving Test Vehicle

Abstract: The response of the contact point of the vehicle with the bridge, rather than the vehicle itself, is proposed for modal identification of bridges by a moving test vehicle. To begin, approximate closed-form solutions were derived for the vehicle and contact-point responses, and they were verified by finite element solutions. The contact-point acceleration is born to be free of the vehicle frequency, an annoying effect that may overshadow the bridge frequencies in case of rough surface. From the frequency respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…The vehicle frequencies are often shown to dominate the overall response (Yang et al, 2013) and can mask the contribution of bridge vibrations to the overall response measured within the vehicle. Yang et al (2018) proposed the use of the response at the point-of-contact between the vehicle tyre and the pavement surface and showed that the contact-point (CP) response was independent of the vehicle frequencies (Yang et al, 2018;Zhang et al, 2018). This was confirmed by in-field testing where a formulation was developed which allowed the CP-response to be derived from the measured response within the vehicle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vehicle frequencies are often shown to dominate the overall response (Yang et al, 2013) and can mask the contribution of bridge vibrations to the overall response measured within the vehicle. Yang et al (2018) proposed the use of the response at the point-of-contact between the vehicle tyre and the pavement surface and showed that the contact-point (CP) response was independent of the vehicle frequencies (Yang et al, 2018;Zhang et al, 2018). This was confirmed by in-field testing where a formulation was developed which allowed the CP-response to be derived from the measured response within the vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…The work by Yang et al is the only known field-test of this approach, however, to extend the approach to more commonly used vehicles, the vehicle suspension and vibration of the vehicle body need to be considered. Since the use of the CP-response was initially proposed by Yang et al (2018) additional numerical studies have been carried out in this area with only one study, by Nayek and Narasimhan (2020), extending the formulation for the CP-response beyond the single degree of freedom model initially proposed by Yang et al (2018). Nayek and Narasimhan (2020) use the CPresponse for a quarter-car model, however they use an inputstate estimation procedure employing a Gaussian process latent force model to estimate the CP-response.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method could not detect the subtle damage on structure. Damage detection methods have also been developed for the identification of damage directly based on measured mode shapes or mode shape curvatures [8][9][10]. A drawback of many mode shape-based methods is the complexity of having measurements from a large number of locations for higher order modal shapes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…By combining the idea of Zhang et al 8 and Oshima et al, 11 Malekjafarian and OBrien 16 utilize an excitation vehicle which can apply a controlled force on bridge structures to indirectly approximate bridge mode shapes with a Hilbert–Huang Transform process similar to Yang et al 10 Numerical simulations indicate that this method is only feasible in the presence of a good quality of road profile and at a low vehicle speed of 2 m/s. Yang et al 17 give a novel method using the contact point acceleration of the vehicle with the bridge for bridge modal identification, but the ability to detect mode shapes decreases when road roughness is considered. He et al 18 extract the first‐order mode shape of a simply supported beam from the acceleration measured on a moving vehicle via HT.…”
Section: Introductionmentioning
confidence: 99%